2016
DOI: 10.1371/journal.pone.0168548
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Associated with Night and Weekend Admissions to ICU with On-Site Intensivist Coverage: Results of a Nine-Year Cohort Study (2006-2014)

Abstract: BackgroundThe association between mortality and time of admission to ICU has been extensively studied but remains controversial. We revaluate the impact of time of admission on ICU mortality by retrospectively investigating a recent (2006–2014) and large ICU cohort with on-site intensivist coverage.Patients and MethodsAll adults (≥ 18 years) admitted to a tertiary care medical ICU were included in the study. Patients' characteristics, medical management, and mortality were prospectively collected. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 62 publications
(81 reference statements)
1
36
1
Order By: Relevance
“…After exclusion of articles during title and abstract screening, we identified 33 articles as eligible. Of these, 23 were adult studies [6][7][8]10,[12][13][14][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and hence excluded (►Fig. for this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After exclusion of articles during title and abstract screening, we identified 33 articles as eligible. Of these, 23 were adult studies [6][7][8]10,[12][13][14][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and hence excluded (►Fig. for this review.…”
Section: Resultsmentioning
confidence: 99%
“…Similar trends of peak mortality during morning hours were reported by adult studies. 13,27,28 Handover time as a risk factor for increased mortality needs to be evaluated further.…”
Section: Time Of the Daymentioning
confidence: 99%
“…The differences in CPR outcomes between the RR and the resident teams might be attributed to either patient-related factors that we were unable to control for, or effects occurring during the night and over weekends. Previous studies have reported that hospitals tend to attend to patients with a greater severity of illness at night; hence, the in-hospital CPR conducted during the night yielded lower ROSC rates [ 10 ]. Further, because these studies [ 11 , 12 ] analyzed the nighttime or weekend effects within the same CPR system, it is likely that patient-related factors and fatigue levels of the medical staff contributed to the lower ROSC rates..…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence as to whether or not patients presenting with acute stroke symptoms receive lower quality of care and have worse outcomes if admitted to hospital outside of normal weekday working hours or at weekends (the ‘weekend effect’). Some studies have shown that acute stroke patients admitted at weekends have lower quality of care1 2 and higher mortality,1–10 while others have shown the opposite 11–14. Evaluation of these studies is further complicated by recent evidence that stroke incidence reporting at the weekend may be unreliable in older studies 15.…”
Section: Introductionmentioning
confidence: 99%